Continuous-flow processes for the S-alkynylation of cysteine-containing peptides and thioglycosides under catalyst-free, oxidant-free and mild conditions. Issue 17 (12th August 2021) - Qin, Long-Zhou; Yuan, Xin; Liu, Jie; Wu, Meng-Yu; Sun, Qi; Duan, Xiu; Zhang, Xin-Peng; Qiu, Jiang-Kai; Guo, Kai
Abstract : Selective S -alkynylation of cysteine-containing peptides and 1-thioglycoside residues was developed using continuous flow. Abstract : Here we developed a novel method involving the use of continuous flow for the selective alkynylation of cysteine-containing peptides and 1-thioglycoside residues. This method was characterised by mild conditions (room temperature, metal-free, oxidant-free conditions), greatly enhancing its usefulness for modifying amino acids and peptides. The newly developed S -alkynylation reagents could apparently reduce the cost and difficulty of the synthesis, thus increasing the sustainability and economy of the process. Moreover, good to excellent yields were obtained for a selection of alkynylated cysteine-containing peptides (35 examples) and 1-thioglycoside residues (15 examples) within short residence times (3–4 minutes).